Structural effects on perovskite phase formation for pzt powders obtained by polymeric precursor method - da Silva, Margarete Soares; da Silva, Lucas Lemos; de Souza, Eliane Ferreira; Ramos, Talita Cuenca Pina Moreira; de Sá, Igor Silva; Barbosa, Graciele Vieira; Longo, Elson [UNESP]; Cavalheiro, Alberto Adriano (Trans Tech Publications, 2018)
Many synthesis methods are available to obtain a set of specific characteristics for lead zirconate titanate (PZT) piezoelectric ceramic powders. In this work, we have successfully prepared PZT powder samples through the Polymeric Precursor Method with x = 0.6, according the general formula Pb(Zrx Ti1-x)O3. The powders were thermally treated from 380 to 550 ºC and characterized by Raman spectroscopy and X-ray diffraction (DRX) in order to evaluate the effects of thermal treatment on the phase formation and the crystallization processes. The results obtained by Raman spectroscopy were compared to refined crystal data obtained by Rietveld method, leading to coherent conclusions about the structural effects occurring along the temperature of calcination. It was possible to characterize the tetragonal perovskite phase as predominant phase occurs only after 500 ºC, but its crystallinity is already determined by synthesis method. Thus, no ordering process is verified for perovskite as a function of the temperature increasing during thermal treatment, in spite of the continuous pyrochlore-to-perovskite phase transition. The pyrochlore secondary phase starts to vanish before its proper crystallization process, changing the tetragonality of previously formed perovskite phase.
Keywords: Crystallization; Phase formation; PZT; Raman; Rietveld; XRD